The validity, objectivity, and reliability of a soccer-specific behaviour measurement tool - Cobb, N. M.; Unnithan, V.; McRobert, A. P. (Science and Medicine in Football, 2018)
Purpose: The purpose of the study was to assess the validity, objectivity, and reliability of a Soccer-Specific Behaviour Measurement Tool (S-SBMT) in relation to the soccer philosophy of a Category One Premier League soccer academy. Methods: A 30 minute, 8 vs. 8 small-sided game (SSG), played by the U12 squad of the participating academy was used for analyses. Validity was ensured through formulating the S-SBMT definitions with experienced soccer coaches from the same soccer academy. Percentage agreement with a reference value of ±1, 95% Confidence Intervals, median sign and Yule`s Q were used to assess objectivity and reliability. Results: High levels of objectivity were found for the number of passes (98.8% agreement), runs with the ball (97.5% agreement), and goal attempts (100%). Reduced objectivity was apparent for forward zonal transitions (75.3%), along with tackles (70.4%), interceptions, (63%), and loose balls (48.1%). Reliability was tested after 1- and 4-weeks, with levels of percentage agreement found to be above the 85% acceptable threshold for most behaviours (passing = 95.1%, runs with the ball = 92.6%, goal attempts = 100%, tackles = 100%). Conclusions: The study demonstrated acceptable objectivity and reliability for S-SBMT behaviours and these findings demonstrate the potential utility of the S-SBMT in monitoring technical actions in a Category One Premier League soccer academy, and a methodological process for other academies to follow in ensuring the quality of performance data.